Innovation in healthy and functional foods - Ghosh, Dilip Kumar (CRC Press, 2013)
"Functional food developers are faced with challenges and opportunities in bringing these food products into the marketplace. This book addresses the latest innovation models, the regulatory framework around innovation, and social issues related to consumer perspectives on innovation versus the need for functional food products. Presented by professionals directly involved in the process, chapters cover food safety, packaging, and regulations; drivers and barriers in innovation; the marketing of functional foods globally; the changing dynamics of food consumption in developing countries; product innovation; technological development; functional food ingredients; and future trends"-- Provided by publisher